Luciferin‐Regenerating Enzyme Mediates Firefly Luciferase Activation Through Direct Effects of D‐Cysteine on Luciferase Structure and Activity. (18th March 2015) - Hemmati, Roohullah; Hosseinkhani, Saman; Sajedi, Reza H.; Azad, Taha; Tashakor, Amin; Bakhtiari, Nuredin; Ataei, Farangis
Abstract Luciferin‐regenerating enzyme (LRE) contributes to in vitro recycling of D‐luciferin. In this study, reinvestigation of the luciferase‐based LRE assay is reported. Here, using quick change site‐directed mutagenesis seven T‐LRE (Lampyris turkestanicusLRE) mutants were constructed and the most functional mutant of T‐LRE (T69R) was selected for this research and the effects of D‐ and L‐cysteine on T69R T‐LRE‐luciferase‐coupled assay are examined. Our results demonstrate that bioluminescent signal of T69R T‐LRE‐luciferase‐coupled assay increases and then reach equilibrium state in the presence of 5 mm D‐cysteine. In addition, results reveal that 5 mm D‐ and L‐cysteine in the absence of T69R T‐LRE cause a significant increase in bioluminescence intensity of luciferase over a long time as well as decrease in decay rate. Based on activity measurements, far‐UV CD analysis, ANS fluorescence and DLS (Dynamic light scattering) results, D‐cysteine increases the activity of luciferase due to weak redox potential, antiaggregatory effects, induction of changes in conformational structure and kinetics properties. In conclusion, in spite of previous reports on the effect of LRE on luciferase bioluminescent intensity, the majority of increase in luciferase light output and time‐course originate from the direct effects of D‐cysteine on structure and activity of firefly luciferase.